Pengaruh Leverage dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan di Sektor Pertanian yang Terdaftar di Bei Periode 2019-2023 - Agus Sanjaya Rumahorbo; M.Noor Armi; Idham Lakoni (Economic Reviews Journal, 2024)
The purpose of this study was to determine how much leverage and profitability affect firm value in companies in the agricultural sector listed on the Indonesia stock exchange for the 2019-2023 period. This type of research uses quantitative research and data sources using secondary data which is explanatory research, and the population of this study is agricultural sector companies in 2019-2023. The sampling technique used purposive sampling method and the data collection technique used documentation and literature study methods. The data analysis technique used is quantitative analysis, classical assumption test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression, multiple correlation, determination test, t test and f test. The results of this study indicate that leverage has a significant effect on firm value, profitability has no significant effect on firm value, and simultaneously leverage and profitability affect firm value.